A Review on Biosurfactant Applications in the Petroleum Industry - Wei Xi; Yuanye Ping; Masoome Agha Alikhani (International Journal of Chemical Engineering)
The inadequacy of worldwide fossil fuel resources, combined with increasing energy demands, encourages global attention to either using alternative energy resources or improving the recovery factor and produce larger quantities from present reservoirs. Among all enhanced oil recovery (EOR) methods, surfactant injection is a well-known technique that reduces the interfacial tension (IFT) between oil and water and increases oil production. Despite numerous advantages of using surfactants, there are also a few obstacles like environmental impacts, high cost, effect on humans and other organisms due to toxicological potential, and availability from nonrenewable resources. Biosurfactants are microbial surface-active agents that decrease the surface tension (ST) of a liquid phase and the IFT of two diverse phases. They are biotechnological products of high value owing to their widespread applications, low toxicity, relatively easy preparation, and specific performance, applied in different industries like organic chemicals and fertilizers, agrochemicals, metallurgy and mining, cosmetics, foods, medical and pharmaceuticals, beverages, environmental management, and petroleum and petrochemical applications in emulsifying and demulsifying wetting agents, detergent spreading and foaming agents, and functional food ingredients. Biosurfactants are synthesized by microbes; therefore, various genetic diversities of microorganisms provide the considerable capability to produce new types of biosurfactants, which can develop EOR technology. Biosurfactants are classified into ex situ and in situ MEOR processes. The genera Pseudomonas, Bacillus, Sphingomonas, and Actinobacteria are the foremost biosurfactant-producing bacteria. This paper reviews relevant reports and results from various presented papers by researchers and companies on applications of microorganisms and biosurfactant technology with specific emphasis on EOR and MEOR processes, based on recently published articles since 2010 until now.